The challenges of implementing an EcoHealth approach to prevention and control of emerging zoonoses in Southeast Asia - Unger, Fred; Lapar, Ma. Lucila; Grace, Delia; Gilbert, Jeffrey (2011)
There is a growing body of support among medical and veterinary communities advocating One Health and other holistic health paradigms as progressive approaches to improving the health of humans, animals and our environment. The International Livestock Research Institute (ILRI) is committed to the potential benefits of the approach. There remains the substantial challenge of how to implement ùon the groundû. Some of the barriers are well described, such as adequate incentive for multiple disciplines to work together (especially biomedical and social sciences), and who will ultimately lead and coordinate such efforts. The EcoHealth Approach to the Prevention & Control of Zoonotic Emerging Infectious Diseases in the Southeast Asia Region (EcoZD) is a 5-and-a-half year project being implemented by ILRI in 6 countries - funded by the International Development Research Centre in Canada. Its core objective is to capacity build researchers and other key actors in the field of emerging zoonoses through applying an EcoHealth approach. In many of the project countries we have identified additional constraints to those described above, such as limited human resources (specifically in areas of technical expertise and language); these same resources overburdened with multiple ODA projects both confined to particular sectors as well as the more progressive inter-sectoral and multi-sectoral ones. The poster will discuss the process of moving from the One Health conceptual framework to practical application by reporting on the progress, lessons learned and particularly ongoing challenges - such as those described above; also whether the priority is 'emerging' zoonoses or 'endemic' (neglected) zoonoses.